Lichen amyloidosis with combined topical therapy: a case report - Indah, Made Sanitca; Puspawati, Ni Made Dwi; Saputra, Herman (Bali Dermatology and Venereology Journal, 2019)
circumscribed, highly pruritic, hyperkeratotic, and hyperpigmented papules occurring typically over the shins, outer aspects of upper arms, and on the upper back with amyloid deposits in the papillary dermis. Several therapeutic strategies, including topical steroids, oral antihistamines, cyclosporine, retinoids, laser, phototherapy, cryosurgery, and surgical interventions, have been reported as treatment options for patients with LA, but no standardized treatment has been established.Case report: A 58-year-old man came to the Dermatovenereology Outpatient Department complaints of itchy blackish-brown papules on the shins. Dermatology examination found discrete multiple hyperpigmentation papules and plaque covered with white scale. A scar-like center surrounded by brownish circles or white edges was found from the dermoscopic examination. The histopathological examination found thickened keratin with compact orthokeratosis and hyaline materials in the papillary dermis with dendritic melanophages. The patient diagnosed with LA and treated by combining desoximetasone cream 0.25% with 3% salicylic acid. The papules on the legs had flattened in the patient, with a significant improvement in the severe itching after three weeks.Conclusion: Combination therapy of potent corticosteroids and keratolytic seems to be an appropriate modality and well-tolerated by LA patients. Skin lesion becomes thinner, and pruritus is reduced.